Religion’s manifold relationship with attitudes toward abortion in the US - Sabriseilabi, Soheil (Journal of contemporary religion, 2025)
Religion is an important factor in shaping people’s emotional response to abortion. The present article conceptualized and operationalized religion as a multidimensional construct. We simultaneously tested the independent effects of four analytically distinguished dimensions of religion (religiosity, spirituality, afterlife beliefs, religious affiliation) on attitudes toward abortion. We also explored the moderating effect of race/ethnicity on the relationship between religion and such attitudes, using data from the General Social Survey of 2018. The results of regression analyses revealed that support for abortion is significantly influenced by religiosity, spirituality, afterlife beliefs, and religious affiliation. Additionally, the findings show that the effect of religiosity and spirituality on abortion attitudes varies across racial or ethnic groups. We discuss the implications of these findings. This issue has gained new currency and urgency after the reversal of the Roe v. Wade ruling by the Supreme Court in 2022.